OX40 Stimulation Enhances Protective Immune Responses Induced After Vaccination With Attenuated Malaria Parasites - Othman, Ahmad Syibli; Franke-Fayard, Blandine M.; Imai, Takashi; van der Gracht, Esmé T. I.; Redeker, Anke; Salman, Ahmed M.; Marin-Mogollon, Catherin; Ramesar, Jai; Chevalley-Maurel, Séverine; Janse, Chris J.; Arens, Ramon; Khan, Shahid M. (Frontiers in Cellular and Infection Microbiology, 2018)
Protection against a malaria infection can be achieved by immunization with live-attenuated Plasmodium sporozoites and while the precise mechanisms of protection remain unknown, T cell responses are thought to be critical in the elimination of infected liver cells. In cancer immunotherapies, agonistic antibodies that target T cell surface proteins, such as CD27, OX40 (CD134) and 4-1BB (CD137), have been used to enhance T cell function by increasing co-stimulation. In this study, we have analyzed the effect of agonistic OX40 monoclonal antibody treatment on protective immunity induced in mice immunized with genetically attenuated parasites (GAPs). OX40 stimulation enhanced protective immunity after vaccination as shown by an increase in the number of protected mice and delay to blood-stage infection after challenge with wild-type sporozoites. Consistent with the enhanced protective immunity enforced OX40 stimulation resulted in an increased expansion of antigen-experienced effector (CD11ahiCD44hi) CD8+ and CD4+ T cells in the liver and spleen and also increased IFN-γ and TNF producing CD4+ T cells in the liver and spleen. In addition, GAP immunization plus α-OX40 treatment significantly increased sporozoite-specific IgG responses. Thus, we demonstrate that targeting T cell costimulatory receptors can improve sporozoite-based vaccine efficacy.